Biomonitoring of toxic and essential trace elements in different tissues of fish species in Turkiye - Turkoglu, Semra; Kaya, Gokce (Taylor & Francis Ltd, 2023)
Concentrations of toxic and essential trace elements (Hg, Ni, Cu, Pb, Cr, Cd, Mn, As and Se) were determined in different tissues (muscle, skin and liver) of three commercial fish species (Diplodus sargus, Zeus faber, Pomatomus saltatrix). The concentration of the elements was measured by ICP-MS. Arsenic was the most accumulated element in fish tissues. As concentrations in tissues of all fish species, except muscle and skin of John Dory fish, were higher than the maximum limits (MLs). The highest Se concentrations in all fish tissues were in found in the liver. Mn levels were higher than the maximum limits in all tissues of Sargoz fish, skin of John Dory fish, livers of Bluefish and Big Bluefish. In addition, Cr concentrations in tissues of all fish species were found to be higher than the maximum limits of FEPA and WHO.
Keywords: Diplodus sargus; Zeus faber; Pomatomus saltatrix; toxic elements; essential trace elements